Staphylococcus aureus bacteremia complicated with non-traumatic mediastinal abscess in children: A case report - Li, Yiyuan; Zhu, Yu; Wan, Chaomin; Wen, Yang (Frontiers in Pediatrics, 2023)
Background: Staphylococcus aureus bacteremia complicated with non-traumatic mediastinal abscess rarely occurs in children. Herein, we report a case of S. aureus bacteremia in a previously healthy 15-month-old boy, which was complicated with a non-traumatic mediastinal abscess, followed by recovery without surgery. Case presentation: A previously healthy 15-month-old boy presented to the hospital with a high fever, accompanied by chills, lethargy, tachycardia, tachypnea, and slight cough. Contrast-enhanced computerized tomography revealed mediastinal abscess and blood culture analysis showed the presence of S. aureus which was methicillin-susceptible. With prompt initiation of antibiotic treatment, with appropriate duration, the patient successfully recovered without surgical drainage upon discharge. Conclusions: Staphylococcus aureus bacteremia complicated with non-traumatic mediastinal abscess is rare in children, and early recognition and appropriate management are essential for a successful outcome.